A Conversational Analysis of Racial Humors Targeting Chinese Characters in “Family Guy” - Syakir, Mochammad Fauzan; Nurfa'ida, Reza; Faiqiah, Nur Layli (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
This research article examines the use of racial humor targeting Chinese characters in the television series